Endoanal resection of rectosigmoid polypoid: lesions by Muldoon’s method - Bermúdez Villegas, Jorge (Cirugía del Uruguay, 1985)
A surgical resection technique is introduced in connection with a series of eight cases of polypoid lesions of the rectosigmoid which by invagination into the rectum allows the exeresis of the lesion.